PERAN NEUROPARENTING DALAM PEMANFAATAN APE UNTUK STIMULASI KOGNITIF ANAK USIA DINI - Faradila, Fitra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to examine in depth the integrative role of the neuroparenting approach and the use of Educational Play Tools (APE) in stimulating the cognitive development of early childhood. Neuroparenting is based on neuroscience, focusing on parenting patterns that are in line with the stages of child brain development, enabling parents to provide optimal and targeted stimulation. The method used is descriptive qualitative with a literature study approach. This study integrates two main theoretical frameworks: Piaget's theory of children's cognitive development stages and Vygotsky's theory, which emphasizes the importance of social interaction and the concept of the Zone of Proximal Development (ZPD). The combination of these theories provides a comprehensive basis for understanding how stimulation that is aware of neurological processes can be mediated through play tools. The results of the theoretical study show that the implementation of the role of neuroparenting in the use of APE can significantly increase the effectiveness of cognitive stimulation. This occurs because multisensory activities and warm emotional interactions, in accordance with the principles of neuroparenting, are able to activate various areas of the child's brain simultaneously and in an integrated manner. This integration also strengthens the vital role of parents as the main facilitators in the process of learning and cognitive development of children. However, this study still has limitations due to its theoretical nature and lack of empirical data from field practice.